The Mechanical Aspects of Formation and Application of PDMS Bilayers Rolled into a Cylindrical Structure - Dongwon Kang; Hyeonji Yu; Jungwook Kim (International Journal of Polymer Science)
A polydimethylsiloxane (PDMS) film with its surface being oxidized by a plasma treatment or a UV-ozone (UVO) treatment, that is, a bilayer made of PDMS and its oxidized surface layer, is known to roll into a cylindrical structure upon exposure to the chloroform vapor due to the mismatch in the swelling ratio between PDMS and the oxidized layer by the chloroform vapor. Here we analyzed the formation of the rolled bilayer with the mechanical aspects: how the mismatch in the swelling ratio of the bilayer induces rolling of the bilayer, why any form of trigger that breaks the symmetry in the in-plane stress level is needed to roll the bilayer uniaxially, why the rolled bilayer does not unroll in the dry state when there is no more mismatch in the swelling ratio, and how the measured curvature of rolled bilayer matches well with the prediction by the theory. Moreover, for the use of the rolled bilayer as the channel of the microfluidic device, we examined whether the rolled bilayer deforms or unrolls by the flow of the aqueous solution that exerts the circumferential stress on the rolled bilayer.